2017
DOI: 10.1088/1361-6501/aa5442
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the dielectric properties of soil under hydraulic loading

Abstract: An experimental set-up was developed in order to determine the coupled hydraulic, dielectric and mechanical properties of granular media under hydraulic loading. The set-up consisted of a modified column for permeability tests involving a flow meter and pressure transducers along the sample to quantify the hydraulic gradient. A newly developed open-ended coaxial probe allowed the measurement of the frequency dependent dielectric permittivity of the material under test. The shear strength of the sample within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The in/outflow of a one-dimensional soil column could be measured using versatile methods: (1) the flow rate logging using flowmeters; (2) the accumulative soil moisture discharge logging by applying conventional TDR analysis for an FRC sensor; (3) the weight logging for the entire soil column or outflow tanks using digital bench scales. The flowmeters have successfully been applied to measure in/outflow rates by many single-phase seepage experiments integrated with the TDR sensor technique in previous studies [ 19 , 20 , 21 , 28 , 83 , 84 ]. All those studies applied a high-precision electromagnetic flowmeter for flow rates logging at higher flow rates, which were generated for a single-phase flow seeping through perfectly spherical glass beads in various sizes under unconsolidated conditions.…”
Section: Soil Accumulative Outflow Measured By Digital Bench Scalesmentioning
confidence: 99%
“…The in/outflow of a one-dimensional soil column could be measured using versatile methods: (1) the flow rate logging using flowmeters; (2) the accumulative soil moisture discharge logging by applying conventional TDR analysis for an FRC sensor; (3) the weight logging for the entire soil column or outflow tanks using digital bench scales. The flowmeters have successfully been applied to measure in/outflow rates by many single-phase seepage experiments integrated with the TDR sensor technique in previous studies [ 19 , 20 , 21 , 28 , 83 , 84 ]. All those studies applied a high-precision electromagnetic flowmeter for flow rates logging at higher flow rates, which were generated for a single-phase flow seeping through perfectly spherical glass beads in various sizes under unconsolidated conditions.…”
Section: Soil Accumulative Outflow Measured By Digital Bench Scalesmentioning
confidence: 99%
“…The third step is the conversion of the dielectric permittivity profile to a porosity profile, n(x), using theoretical mixing equations. Prior studies indicated the applicability of the Lichtenecker-Rother model (Bittner et al, 2017(Bittner et al, , 2019 for saturated glass beads, where the dielectric permittivity of the mixture is computed as the weighted sum of the dielectric permittivity of the water and glass beads by their respective volume fraction:…”
Section: Coaxial Erosion Cellmentioning
confidence: 99%
“…Test samples were prepared with soda-lime glass beads as an idealised granular soil. The suitability and advantages of using glass beads as a replacement material for soil has been highlighted in several prior studies (Tomlinson and Vaid, 2000;Scheuermann, 2012;Zakaraya Alhasan et al, 2015;Bittner et al, 2017). From the perspective of spatial TDR, an additional benefit of considering glass beads is the constant dielectric permittivity of the glass beads, as well as the fact that mineralogy of real soil particles do not have to be taken into account.…”
Section: Materials and Sample Configurationmentioning
confidence: 99%